The subcutaneous ld50 of Ivalin, extracted and purified from Geigeria aspera, in two murine models - Botha, C.J. (Christoffel Jacobus) (University of Pretoria, 2025)
Mini Dissertation (MMedVet (Toxicology))--University of Pretoria, 2024.